POTENSI KULTUR SEKOLAH DALAM PENGINTEGRASIAN KONTEN PENDIDIKAN MULTIKULTURAL DI SEKOLAH MENEGAH ATAS NEGERI 3 DENPASAR - Ni Wayan Yuli Lestari; Ferdinandus Nanduq; Komang Trisnadewi (Guna Widya: Jurnal Pendidikan Hindu, 2023)
Multicultural education is an education that respects the differences of various cultural groups. At SMA Negeri 3 Denpasar there are various students. Therefore, multicultural education is important to implement. This is because there are still various cases of violence and bullying that occur, especially in SMA Negeri 3 Denpasar. So it is important for schools to apply the values ​​of multicultural education to strengthen school culture. The problems discussed in this study are (1) How is the potential form of school culture in integrating multicultural education content at SMA Negeri 3 Denpasar, (2) How is the empowerment of school culture potential in integrating multicultural education content at SMA Negeri 3 Denpasar. The theory used in this research is the theory of multicultural education and the theory of social learning. Data collection methods used are non-participant observation, structured interviews, literature study and document study. The data that has been obtained were analyzed by qualitative descriptive analysis method. The results showed that (1) The potential form of school culture in integrating multicultural education content at SMA Negeri 3 Denpasar can be seen in the school climate, intellectual climate, rules and policies, traditions and routines, school organizational structure, effective partnering and character norms. (2) Empowering the potential of school culture in integrating multicultural educational content at SMA Negeri 3 Denpasar can be done by means of communication interactions, creating a clean and conducive environment, making extracurricular activities, making competition activities, providing classrooms and libraries as places for learning and reading, providing warnings or sanctions for students who violate school rules, carrying out prayers, mutual cooperation activities and providing trash bins, holding the election of the student council president and class apparatus and holding committee meetings, obeying norms and mutual respect and respect among school members.